Amazon Biobank - A community-based genetic database - Kimura, Leonardo T.; Andrade, Ewerton R.; Carvalho, Tereza C.; Simplício Junior, Marcos A. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2021)
In regions like the Amazon Rainforest, there is much unexplored biodiversity data that could potentially be used to promote innovative biotechnology developments. Building a biobank with such genetic data is, however, a challenge. One reason is that existing repositories (e.g., NCBI) lack clear incentives for collaboration. Aiming to tackle this issue, and promote a biodiversity-based economy in the Amazon region, in this work we present a prototype for the Amazon Biobank, a community-based genetic database. Leveraging blockchain, smart contracts, and peer-to-peer technologies, we build a collaborative and highly scalable repository. It also enables monetary incentives for users who insert, store, process, validate and share DNA data.